sistemática de literatura Financial literacy with gender perspective: systematic literature review - Bayly Castañeda, Karla Patricia; Ramírez-Montoya, María Soledad; Morita Alexander, Adelina (IE Revista de Investigación Educativa de la REDIECH, 2023)
Sustainable development within the framework of the 2030 Agenda proposed by UNESCO requires the integration of women as key players, not only in production processes but also in social and economic ones. That is why financial inclusion becomes relevant as a tool to reduce the gender gap, one of the main barriers to such integration. The purpose of this research is to analyze not only the factors that generate inequality and financial exclusion but those that may be able to reduce it, emphasizing education and the characteristics to consider during the design of a financial education training process with a gender perspective. For this reason, a systematic literature review was performed to critically analyze 31 research studies on financial inclusion and gender gap, extracted from the Scopus and Web of Science (WoS) databases. Inclusion and exclusion criteria were applied, as well as data extraction and information synthesis process following the prisma model to answer six research guide questions.